Buah Apel (Romebeauty) Menurunkan Kadar Gula Darah Pasien Diabetes Mellitus - Harmayetty Harmayetty; Yulis Setiya Dewi; Dwi Astutik (Universitas Airlangga, 2007)
Introduction: The number of patients with diabetes mellitus (DM) in year 2001 was 5.6 million. In the year 2020, it is expected to reach 8.2 million. The diet of DM patients in Pulorejo village comprised low calorie, sugar free, and low fiber diet. Fiber consumed by these patients was taken from vegetables and banana. Unfortunately, the use of such diet keep the patient's blood sugar level remains increasing. The content of water-soluble fiber (pectin) in apple is higher and is able to reduce blood sugar level. The objective of this study was to analyze the effect of apple consumption on blood sugar level. Method: This study was used a quasy-experimental pre-post test purposive sampling design. Samples who met to the inclusion criteria were 14 persons divided into treatment and control group. Data were analyzed by using Paired t-Test (α=0.05) and Independent t-Test (α=0.05). Result: The result showed that there was an effect of apple consumption on blood sugar level with Paired t-Test (p=0.000) for blood glucose level before and after intervention in treatment group, and (p=0.100) for blood glucose level before and after intervention in control group. The results of Independent t-Test revealed p=0.000 for blood glucose level after intervention in treatment and control groups. Discussion: It’s can be concluded that there was an effect of apple consumption on blood sugar level in DM patients. The apple should be given in the best dose that can reduce blood sugar level, which is 2 x 150 g. The result of this study can be considered in as a material for diet promotion for the patients. Further studies should be developed to measure the variables of stress and sex of the patients.